2013
DOI: 10.1088/0004-637x/769/1/77
|View full text |Cite
|
Sign up to set email alerts
|

Moa-2010-BLG-311: A Planetary Candidate Below the Threshold of Reliable Detection

Abstract: We analyze MOA-2010-BLG-311, a high magnification (A max > 600) microlensing event with complete data coverage over the peak, making it very sensitive to planetary signals. We fit this event with both a point lens and a two-body lens model and find that the two-body lens model is a better fit but with only Δχ 2 ∼ 80. The preferred mass ratio between the lens star and its companion is q = 10 −3.7±0.1 , placing the candidate companion in the planetary regime. Despite the formal significance of the planet, we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Our choice of ∆χ 2 threshold is the de facto standard among microlensing simulations (e.g., Bennett & Rhie 2002;Bennett et al 2003;Penny et al 2013;Henderson et al 2014a). Yee et al (2012) and Yee et al (2013) discussed the issue of the detection threshold in survey data for high magnification events, and concluded that for one particular event a clear planetary anomaly in the full data set might be marginally undetectable in a truncated survey data set at ∆χ 2 ≈ 170. For a uniform survey data set, and a search that included low-magnification events, Suzuki et al (2016) used a ∆χ 2 threshold of 100.…”
Section: Simulating the Wfirst Microlensing Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Our choice of ∆χ 2 threshold is the de facto standard among microlensing simulations (e.g., Bennett & Rhie 2002;Bennett et al 2003;Penny et al 2013;Henderson et al 2014a). Yee et al (2012) and Yee et al (2013) discussed the issue of the detection threshold in survey data for high magnification events, and concluded that for one particular event a clear planetary anomaly in the full data set might be marginally undetectable in a truncated survey data set at ∆χ 2 ≈ 170. For a uniform survey data set, and a search that included low-magnification events, Suzuki et al (2016) used a ∆χ 2 threshold of 100.…”
Section: Simulating the Wfirst Microlensing Surveymentioning
confidence: 99%
“…There is also significant work needed on microlensing simulations to better understand the information that WFIRST will be able to measure for each planet it finds. This is especially the case for host mass measurements, which will be possible though one or more of the techniques: detecting the host as it separates from the source and measuring image elongation, color-dependent centroid shifts or directly resolving the lens (e.g., Bennett et al 2007;Henderson 2015;Bhattacharya et al 2017), measuring the microlensing parallax with or without finite source measurements (e.g., Yee et al 2013;Yee 2015;Bachelet et al 2018), or even measuring astrometric microlensing (Gould & Yee 2014). The error budget of these measurements is likely to be dominated by systematic errors, and so more detailed end-to-end simulations of the stacking, photometry and astrometry pipelines are likely necessary in order to fully understand WFIRST's capabilities.…”
Section: Future Improvementsmentioning
confidence: 99%
“…where k is a linear scaling factor and e min a minimum error added in quadrature. In A1999 the traditional metric of forcing χ 2 /dof = 1 for each dataset (Yee et al 2013) was used to arrive at a k ∼ 1.8, with the e min remaining unused. However as in Bachelet et al (2018) we avoid using this determination as it is is only relevant for linear models (Andrae et al 2010).…”
Section: Error-bar Rescalingmentioning
confidence: 99%
“…For both models, we use χ 2 criterion to test the detectability of a planetary signal. This criterion is based on the difference between χ 2 of two models; We accept the hypothesis of an exoplanet detection whenever ∆χ 2 150 which is a reasonable threshold for space-based telescopes (Bennett & Rhie 2002; Penny et al 2019;Bennett et al 2003;Penny et al 2013;Henderson et al 2014;Yee et al 2012Yee et al , 2013.…”
Section: Detectability Of the Simulated Eventsmentioning
confidence: 99%